A critical tax theory approach to income tax relief for black-middle class taxpayers contributing to the support of family - Ndebele, Zandile (Department of Commercial Law, 2022)
The purpose of this thesis is to examine income tax relief measures for taxpayers with dependants in South Africa. This research has found that taxpayers who are black and middle-class are likely to make contributions to the support of household member and non-household member dependants. This is also supported by literature from the United States, where black middle-class individuals are found to make significant contributions towards the support of their kin when compared to other races. This support which a black middle-class taxpayer gives to their dependants entwines with their ability-to-pay in tax law. A taxpayer's ability-to-pay is reduced by the contributions made to their dependants. For this reason, it is relevant to examine the intersectionality of race, class, and family circumstances with tax law. The black middle-class are an interesting demographic in South Africa and are referred to as a “precariat class” because of the uncertainty and insecurity linked to this class. In 2021, the black middle-class carry a burden to contribute towards the support of dependants. This burden was imposed on them first by apartheid policies which excluded black South Africans from receiving social welfare assistance and then by racial and economic inequalities in post-apartheid South Africa. Through discussions on social justice and tax equity, the thesis finds a basis for income tax relief measures for taxpayers with dependants in South Africa. The introduction of such a tax system would allow the black middleclass taxpayers to take advantage of the income tax benefits. The definition of family and the definition of a dependant in allowing for the income tax benefits will be important. These definitions should reflect the meaning of family as understood by South African taxpayers. That way, the disparate impact, and unintended consequences of the income tax benefits on those that use these benefits are avoided to an extent.